28th International Symposium on Automation and Robotics in Construction (ISARC 2011) 2011
DOI: 10.22260/isarc2011/0050
|View full text |Cite
|
Sign up to set email alerts
|

ICT Adoption in the Iranian Construction Industry: Barriers and Opportunities

Abstract: ABSTRACT:In the competitive market of the construction industry, construction firms attempt to implement the projects with the least cost and time, and the highest quality. They try different ways to increase the efficiency of their projects. One of the most important factors which affects the efficiency of construction projects is Information and Communication Technology (ICT) utilization in construction. There are many software and hardware which have been developed to help planning, designing and executing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…This is coupled with the fact that an analysis of whether tech tools fit in with existing company practices and policies is needed. This finding is in line with the submissions of Alaghbandrad et al (2011) andHlahla (2013) who noted the possible rejection of technology in the industry as a crucial risk that may deter its successful implementation.…”
Section: Discussionsupporting
confidence: 88%
“…This is coupled with the fact that an analysis of whether tech tools fit in with existing company practices and policies is needed. This finding is in line with the submissions of Alaghbandrad et al (2011) andHlahla (2013) who noted the possible rejection of technology in the industry as a crucial risk that may deter its successful implementation.…”
Section: Discussionsupporting
confidence: 88%
“…but I perceive that it would make things very easy". Alaghbandrad et al (2011) also found that training outside the construction company is not as efficient as inside classes. Therefore, some construction professionals have had to learn more in universities to know what they do in the CI.…”
Section: Causes Of Underutilisation Of Information Communication Tech...mentioning
confidence: 99%
“…According to Alaghbandrad et al (2011), it has been revealed that some leading construction firms in ICT consider ICT skills as a requirement for job applicants in the CI, and that this has encouraged the architects, engineers, etc. to learn ICT skills before their employment.…”
Section: Effects Of the Underutilisation Of Information Communication...mentioning
confidence: 99%
“…It was noted that the aspect of resistance to use involves negative reactions to the implementation of BDA. Several studies have affirmed that resistance from the workforce and unions is a crucial factor affecting the adoption of digital technologies such as BDA within the construction industry (Alaghbandrad, et al, 2011;Vaduva-Sahhanoglu, Calbureanu-Popescu, and Smid, 2016;Oke, et al, 2018;Ikuabe, et al, 2020). Similarly, the introduction of innovative processes and technologies such as BDA that threaten processes that work or have been working for years is often perceived as a risky act (Hwang, Trupp, and Liu, 2003;Vass and Gustavsson, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%